Analgetic Effects of Kangkung (Ipomea reptans Poir) Extract on Swiss Webstesr Mice - Handayani, Andi Ika Julianti; Hidayat, Saepul (iora, 2024)
One of the efficacious plants as an empirical analytic is kangkung (Ipomea reptans Poir). The purpose of this study was to determine the analgesic effect of kangkung and determine the dose of kangkung extract compared to ibuprofen. The benefit of this research is to know the analgesic effect of kangkung extract. The contents of extract kangkung are flavonoids. The research method of this experimental test is divided into 5 groups, each group consisting of 5 mice with weight 20-30 grams and age 2-3 months. Group 1 Negative control (Aquadest), group II Positive control (the suspension of ibuprofen), group III, IV, and V respectively were given the ground kangkung extract dose 6 mg/30 g, 12 mg/30 g, 24 mg/30 g. The treatment is administered orally, and for the introduction of the induction using acetic acid 0.5% dose 0.2 ml/20 g mice are intraperitonial. The result of analyzed by Test homogeneity followed by a Variant analyze Test (ANOVA) one way with SPSS for window version 16. The homogenized results of the research of extract kangkung land extract (P = 0.24), a one-way test is obtained significant result 0.00, the dose I, II, III differs significantly with negative and positive control. Conclusion of the ground Kangkung extract has an analytic effect by lowering the amount of stretched. The results showed at a dose of 28 mg/30 g mice caused the best analytic effect among the variations of the dose tested.